SERS Platform Based on Bimetallic Au-Ag Nanowires-Decorated Filter Paper for Rapid Detection of miR-196ain Lung Cancer Patients Serum - Ji Xia; Yifan Liu; Menglin Ran; Dan Lu; Xiaowei Cao; Youwei Wang (Journal of Chemistry)
Detecting microRNA (miRNA) biomarkers expression is of great significance for the diagnosis and treatment of lung cancer. Surface-enhanced Raman scattering (SERS) has achieved microRNA sensing for the diagnosis of primary liver cancers. In this work, we developed a SERS technology for the rapid detection of lung cancers-related miRNA (miR-196a) using bimetallic Au-Ag nanowire (AgNW@AuNPs) substrates coupled with the target hairpin DNA. The finite-difference time-domain simulation proved that a large number of “hot spots” were generated between the AgNW and AuNPs, which resulted in a huge enhancement of the signal of Raman reporters. Filter paper treated by hexadecenyl succinic anhydride hydrophobic and modified with AgNWs@AuNPs was used as capturing substrate. The detection limits of miR-196a in PBS and serum were as low as 96.58 aM and 130 aM, respectively. Studies on nonspecific sequence and single-base mismatch of miRNA demonstrated that SERS-based platform was highly selective, excellent uniform, and reproducible. Finally, the platform was used to show that the miR-196a expression in the serum of lung cancer patients was much higher than that in healthy people. The detection results indicated that the SERS platform had potential applications in cancer diagnosis and might be a viable alternative to the conventional miRNA detection method, the real-time polymerase chain reaction (RT-PCR) technology.